Does It Still Show a Deficit? Arguing Post-COVID-19 Health Financing System in Bogor, Indonesia - Veruswati, Meita; Asyary, Al; Alnur, Rony Darmawansyah; Sagala, La Ode Hasnuddin S; Guspianto, Guspianto; Herawati, Maria Holy (Kesmas, 2022)
Before the COVID-19 pandemic, the Bogor City Government regulated to cover the health financing claim during the Indonesian National Health Insurance (NHI) integration period due to the lower amount of health care claim per episode in regional hospitals compared to ones that NHI paid. This study aimed to address post-COVID-19 health financing at two hospitals in Bogor City, West Java Province, Indonesia. Descriptive analysis using the aggregate statistical summaries was taken to explore the medical care episodes of the data series at two hospitals for the last two years. Of the 890 checked medical records data, the deficit occurred in 197 (22.1%) medical care episodes, while five (0.6%) exceeded the hospitals' tariffs. The remaining 688 (77.3%) medical care episodes had suits with the Indonesian-Case Based Groups. Almost a quarter of medical care episodes in aggregate experienced a deficit in the two years before the pandemic. This study is the first to provide new insight into the discussion on medical care financing in a developing country's post-pandemic era in a newly implemented NHI system.